2018
DOI: 10.12688/wellcomeopenres.12841.2
|View full text |Cite
|
Sign up to set email alerts
|

EnLightenment: High resolution smartphone microscopy as an educational and public engagement platform

Abstract: We developed a simple, cost-effective smartphone microscopy platform for use in educational and public engagement programs. We demonstrated its effectiveness, and potential for citizen science through a national imaging initiative, . The cost effectiveness of the instrument allowed for the program to deliver over 500 microscopes to more than 100 secondary schools throughout Scotland, targeting 1000's of 12-14 year olds. Through careful, quantified, selection of a high power, low-cost objective lens, our smartp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…The incorporation of the lens into the smartphone has turned this combination into a portable microscope. Several smartphone-based microscopes have been used in detecting detailed images such as human cells and parasites [ 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…The incorporation of the lens into the smartphone has turned this combination into a portable microscope. Several smartphone-based microscopes have been used in detecting detailed images such as human cells and parasites [ 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous work has indicated that for 10 µL heat cured PDMS lenses, a temperature of 200°C gives rise to the greatest contact angle and magnification [25]. Additionally, this lens offers sufficient resolution for histological [25] and bacteriological imaging [21,28]. Smartphone microscopy systems have been developed with a resolution compatible with viruses and 100 nm nanoparticles, yet the use of laser diode light sources and expensive external lenses [29] may make cost a prohibitive factor for translation to a low resource setting.…”
Section: Introductionmentioning
confidence: 99%
“…It is a playful educational tool capable of observing the structure and dynamic behavior of live microorganisms [2]. Another simple, cost-effective smartphone microscope platform has been developed for secondary and high school students to obtain research-level images of parts of insects, pollen grains, and sodium chloride crystals [3]. One type of smartphone microscope is capable of identifying red and white blood cells in blood smears and soil-transmitted helminth eggs in stool samples [4], and another smartphone microscope has been used to detect malaria in fixed and stained blood smears [5,6].…”
Section: Introductionmentioning
confidence: 99%